Advancing Autism Research From Mice to Marmosets: Behavioral Development of Offspring Following Prenatal Maternal Immune Activation - Santana-Coelho, Danielle; Layne-Colon, Donna; Valdespino, Roslyn; Ross, Corinna C.; Tardif, Suzette D.; O'Connor, Jason C. (Frontiers in Psychiatry, 2021)
Understanding the mechanism(s) by which maternal immune activation (MIA) during gestation may disrupt neurodevelopment and increase the susceptibility for disorders such as autism spectrum disorder (ASD) or schizophrenia is a critical step in the development of better treatments and preventive measures. A large body of literature has investigated the pathophysiology of MIA in rodents. However, a translatability gap plagues preclinical research of complex behavioral/developmental diseases and those diseases requiring clinical diagnosis, such as ASD. While ideal for their genetic flexibility, vast reagent toolkit, and practicality, rodent models often lack important elements of ethological validity. Hence, our study aimed to develop and characterize the prenatal MIA model in marmosets. Here, we adapted the well-characterized murine maternal immune activation model. Pregnant dams were administered 5 mg/kg poly-L-lysine stabilized polyinosinic-polycytidylic acid (Poly ICLC) subcutaneously three times during gestation (gestational day 63, 65, and 67). Dams were allowed to deliver naturally with no further experimental treatments. After parturition, offspring were screened for general health and vigor, and individual assessment of communication development and social behavior was measured during neonatal or adolescent periods. Similar to rodent models, offspring subjected to MIA exhibited a disruption in patterns of communication during early development. Assessment of social behavior in a marmoset-modified 3-chamber test at 3 and 9 months of age revealed alterations in social behavior that, in some instances, was sex-dependent. Together, our data indicate that marmosets are an excellent non-human primate model for investigating the neurodevelopmental and behavioral consequences of exposure to prenatal challenges, like MIA. Additional studies are necessary to more completely characterize the effect of prenatal inflammation on marmoset development and explore therapeutic intervention strategies that may be applicable in a clinical setting.